2016
DOI: 10.1115/1.4033504
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Architectural Complexity for Product Family and Platform

Abstract: A product family is a set of products that are derived from common sets of parts, interfaces, and processes, known as the product platform. To reduce development time and procurement and operating costs of product platform-based variants, the product platform can be designed after consideration of several characteristics, such as modularity, flexibility, sustainability, and complexity. In this paper, the product platform is viewed from the perspective of system architecting. The architectural complexities of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Tamaskar et al (2014) demonstrated the use of their metric on space satellite application. Complexity metrics developed in Sinha and de Weck (2013) were utilized for system architectural configuration complexity assessment (Min et al 2016), technology infusion impact on system complexity (Min et al 2015), and product platform complexity assessment (Kim et al 2016). …”
Section: Previous Research 21 System Complexitymentioning
confidence: 99%
“…Tamaskar et al (2014) demonstrated the use of their metric on space satellite application. Complexity metrics developed in Sinha and de Weck (2013) were utilized for system architectural configuration complexity assessment (Min et al 2016), technology infusion impact on system complexity (Min et al 2015), and product platform complexity assessment (Kim et al 2016). …”
Section: Previous Research 21 System Complexitymentioning
confidence: 99%
“…In this section, we demonstrate the proposed method via a case study of the patent search for spherical rolling robots (SRRs) from the USPTO patent database. SRRs are spherical shape robots that can propel themselves to roll around on the ground (Bicchi et al, 1997;Kim et al, 2016), and have been developed for defence and surveillance applications (Wu et al, 2017) and as toys and other consumer applications. An of example SRR is presented in Figure 4.…”
Section: Figure 2 An Example Run Of Phrase Extraction Processmentioning
confidence: 99%
“…Some recent publications extended product platform design and optimization framework to incorporate supply chain, as the platform itself and product variants inevitably affect supply chain operation and costs . Other recent advances in product platform‐related research include establishing a relationship between the product platform and inherent system attributes, such as complexity and changeability, which can be used to optimize product platforms for additional system attributes in addition to commonality and modularity.…”
Section: Literature Reviewmentioning
confidence: 99%